2021
DOI: 10.1103/physrevb.103.134103
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced bcc-rhombohedral phase transition in vanadium metal

Abstract: Vanadium is reported to undergo a pressure-induced bcc-rhombohedral phase transition at 30-70 GPa, with a transition pressure that is sensitive to the hydrostaticity of the sample environment. However, the experimental evidence for the structure of the high-pressure phase being rhombohedral is surprisingly weak. We have restudied vanadium under pressure to 154 GPa using both polycrystalline and single-crystal samples, and a variety of different pressure transmitting media (PTM). We find that only when using si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…which are all in a good agreement with our results, in considerations of the deviations among the measured pressures being of ∼ 2 GPa. It is noticeable that the RH 2 → BCC → RH 1 transition sequence, neither observed in earlier experiments nor proposed by previous computations, was observed in the one of the latest experiments[20], and the measured transition pressure of RH 2 , 40 GPa, coincides with our theoretical one, 44 GPa. When the pressure is increased larger than 132 GPa, our results indicate that RH 1 would exist until RH 2 transition occurs at 154 GPa and the RH 2 phase keeps stable with the pressure up to 254 GPa, over which the BCC may coexist with RH 2 until the pressure increases up to 280 GPa when BCC becomes the most stable for higher pressures.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…which are all in a good agreement with our results, in considerations of the deviations among the measured pressures being of ∼ 2 GPa. It is noticeable that the RH 2 → BCC → RH 1 transition sequence, neither observed in earlier experiments nor proposed by previous computations, was observed in the one of the latest experiments[20], and the measured transition pressure of RH 2 , 40 GPa, coincides with our theoretical one, 44 GPa. When the pressure is increased larger than 132 GPa, our results indicate that RH 1 would exist until RH 2 transition occurs at 154 GPa and the RH 2 phase keeps stable with the pressure up to 254 GPa, over which the BCC may coexist with RH 2 until the pressure increases up to 280 GPa when BCC becomes the most stable for higher pressures.…”
supporting
confidence: 79%
“…Akahama et al [19] compressed foil V up to 300 GPa at room temperature and found that BCC lattice is a stable phase until the RH 2 and BCC phase coexisting at pressure (P ) larger than 242 GPa, while the RH 1 phase is a metastable phase caused by nonhydrostatic pressure effects. Stevenson et al [20], on the other hand, observed that the BCC lattice transform into RH 2 when P > 40 GPa and then turns back to BCC until RH ), which is significantly different from the theoretical result, 110.5 • (or 108.5 • ) for RH 1 (or RH 2 ).…”
mentioning
confidence: 72%
See 3 more Smart Citations